2008
DOI: 10.1029/2007jg000596
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and temporal rainfall variability near the Amazon‐Tapajós confluence

Abstract: [1] Do the influences of river breezes or other mesoscale effects lead to a systematic river proximity bias in Amazon rainfall data? We analyzed rainfall for a network of 38 rain gauges located near the confluence of the Tapajós and Amazon rivers in the eastern Amazon Basin. Tipping bucket rain gauges worked adequately in the Amazon rainfall regime, but careful field calibration and comparison with collocated conventional rain gauges were essential to incorporate daily totals from our array into regional maps.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
93
0
13

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 85 publications
(114 citation statements)
references
References 62 publications
(82 reference statements)
8
93
0
13
Order By: Relevance
“…Our synthetic decade-long rainfall record corresponded closely with the nearby INMET Belterra measurements, although INMET Belterra had on average 220 mm of rainfall more per year, likely due to differences in circulation and convection between the km67 forest and Belterra pasture land surface (Fitzjarrald et al, 2008). Annual rainfall (Fig.…”
Section: Meteorological Measurements and Droughtmentioning
confidence: 65%
See 1 more Smart Citation
“…Our synthetic decade-long rainfall record corresponded closely with the nearby INMET Belterra measurements, although INMET Belterra had on average 220 mm of rainfall more per year, likely due to differences in circulation and convection between the km67 forest and Belterra pasture land surface (Fitzjarrald et al, 2008). Annual rainfall (Fig.…”
Section: Meteorological Measurements and Droughtmentioning
confidence: 65%
“…We discarded site-based data and calculated a distance-weighted synthetic hourly rainfall time series from a network of nearby meteorological stations, with locations ranging from 10 to 110 km away from km67. More information on the meteorological network is available in Fitzjarrald et al (2008). Detailed information about the subsequent calculations of the synthetic precipitation data set and PAR drift correction are available in Longo (2014).…”
Section: Meteorological Measurementsmentioning
confidence: 99%
“…Dos Santos et al (2014) used satellite rainfall products to define the features of river breezes associated with the Negro, Solimões, and Amazon rivers. Fitzjarrald et al (2008) have described the effect of the Tapajos River on rainfall, and Silva have shown how wind structure favours cloud formation on the upwind side of the Tapajós River during daytime. Negri et al (2000) used passive microwave radiances to construct a 10-year climate related to the Amazonas rainfall patterns.…”
Section: Knowledge About Cloud Process In the Amazon Acquired During mentioning
confidence: 99%
“…The diurnal convection cycle is strongly linked to underlying surface features Silva Dias et al, 2002), including its topography , deforestation (Saad et al, 2010), and large rivers (Dos Santos et al, 2014;Silva Dias et al, 2004). Additionally, large rivers impact the evolution of rainfall through the convergence of river breezes with ambient air flow (Fitzjarrald et al, 2008). Adams et al (2015) have shown that one central problem of the climate model related to the Amazon's diurnal convection and rainfall variability is the transition from shallow to deep convection, which occurs on a timescale of a few hours.…”
Section: The Amazon Forest Climatementioning
confidence: 99%
“…The diurnal cycle of convection has a strong link to the underlying surface: its topography (Laurent et al 2002), deforestation (Saad et al 2010) and large rivers , demonstrating a link to surface features . Additionally, large rivers impact rainfall evolution through the convergence of the river breeze with ambient flow (Fitzjarrald et al 2008). Adams et al (2016) showed that one 25 of the climate models central problem related to Amazon diurnal variability of convection and rainfall is the transition from shallow to deep convection, which occurs on a time scale of approximately three hours.…”
Section: -The Amazon Forest Climatementioning
confidence: 99%